Varied Macro- and Micronutrient Fertilization Rates Impact Root Growth and Distribution and Fruit Yield of Huanglongbing-affected Valencia Orange Trees - Davie M. Kadyampakeni; Tanyaradzwa Chinyukwi; Samuel Kwakye; Lorenzo Rossi (HortScience, 2023)
Candidatus Liberibacter asiaticus (CLas), which causes huanglongbing (HLB) in citrus trees, has a great impact on tree root health, fruit development, and juice quality. HLB-affected trees have a fibrous root density loss of ∼30% to 80%, resulting in the limited capacity of citrus trees to uptake nutrients. Therefore, this study was conducted for 3 years to 1) assess the temporal changes in root density as a result of varied fertilization, 2) determine dynamics of HLB with regard to root growth and distribution as a result of varied fertilization for Valencia orange trees, and 3) evaluate the impact of varied fertilization rate and method of fertilization on fruit yield for HLB-affected trees. Macronutrients and micronutrients were applied at varying fertilization rates (0×, 1×, 2×, and 4×, of University of Florida guidelines). Root scans were done using minirhizotrons at 0 to 19.1 cm, 19.1 to 40.7 cm, 38.2 to 59.8 cm, and 57.3 to 78.9 cm soil depths. Results obtained from the study showed that root growth and distribution were greater in 0 to 19.1 cm than 19.1 to 40.7 cm to 57.3 to 78.9 cm soil depths. Thus, root growth decreased (P < 0.0004) with increasing soil depth due to variation in nutrient availability for tree uptake. Increased nutrient availability at occurrence of physiological processes in citrus trees also influenced root growth and distribution, resulting in root growth flushes in the months of Nov to early Feb and Jul to early Aug. Fruit yield was significantly different between treatments in 2 of the 4 years of the study (P = 0.001 and P = 0.003), and largely ascribed to soil fertilization of micronutrients compared with foliar. Therefore, at higher fertilization rates, particularly via soil application, nutrient availability was increased, thus promoting root growth and distribution and fruit yield in HLB-affected orange trees.